Coexistence of cervical endometriosis with premalignant and malignant gynecological pathologies: report on a series of 27 cases. Issue 9 (21st October 2021) - Matalliotakis, Michail; Matalliotaki, Charoula; Zervou, Maria I.; Krithinakis, Konstantinos; Kalogiannidis, Ioannis; Goulielmos, George N.
ABSTRACT: Although cervical endometriosis represents a rare condition, there is evidence that implicates a complex interaction with other gynecological pathologies. This study aims to highlight this entity and further to explore the impact of oncological pathology of female genital tract on patients with cervical endometriosis. We retrospectively investigated the medical and pathological reports of 27 cases with cervical endometriosis, which were diagnosed by tissue biopsy. The results of the study show a relationship between CIN (cervical intraepithelial neoplasia) cases 19/27 (70percent) and cervical endometriosis. CIN I was more frequently found compared to patients with CIN II and CIN III. Furthermore, a high prevalence of HPV (human papilloma virus) was confirmed. Out of 27 patients, 2 cases with cervical (7.4percent), 2 with endometrial (7.4percent) and 3 with ovarian cancer (11.1percent) were detected. We confirmed the coexistence of more than one malignant gynecological pathology with cervical endometriosis in four cases (14.8percent). To conclude, cervical endometriosis is a rare disease co-existing considerably with premalignant and malignant gynecological conditions according to our data. Although the pathophysiology and genetics of cervical dysplasia is well delineated, further research is needed to establish the association between cervical endometriosis and gynecological premalignant and malignant pathology.